Occupational Similarity and Spousal Support: A Study of the Importance of Gender and Spouse's Occupation - Wallace, Jean; Jovanovic, Alyssa (Relations industrielles / Industrial Relations, 2011)
This paper examines how gender and the occupation of one's spouse may explain differences in the amounts and types of spousal support individuals receive when coping with the stress of their job. We analyze survey data from a sample of married lawyers, some of whom are married to other lawyers and others who have spouses who are not lawyers. The results show that men receive more emotional support from their spouse than women, regardless of their spouse's occupation. In contrast, lawyers receive more informational support from their spouse if they are also a lawyer, regardless of their gender. These fi ndings suggest that wives provide more understanding and empathy to their spouses than husbands, consistent with the literature on gender diff erences in social support. Our fi ndings also suggest that when it comes to providing informational support in terms of sharing advice, suggestions, solutions or relevant experiences in solving a work-related problem, a spouse who is in the same occupation may be better able to provide support. This is consistent with the literature demonstrating the importance of shared experiences in understanding the eff ectives of social support. Future research might explore not only the importance of shared statuses, such as occupation, but also the meaning of shared experiences in order to better understand spouses' support of one another.